Factors predisposing to intraoperative floppy-iris syndrome: An up-to-date meta-analysis. Issue 11 (November 2022) - Christou, Chrysanthos D.; Esagian, Stepan M.; Ziakas, Nikolaos; Prousali, Efthymia; Tzamalis, Argyrios
Abstract : Although tamsulosin remains the major factor predisposing to IFIS, significant correlations with other factors also exist, such as decreased pupil diameter and the intake of finasteride, benzodiazepines, and antipsychotic agents. Abstract : Intraoperative floppy-iris syndrome (IFIS) is an increasingly recognized condition that is proven to lead to higher rates of intraoperative complications. This study provides an updated systematic review and meta-analysis regarding all the identified factors predisposing to IFIS. The study was performed in accordance with the PRISMA guidelines. 38 studies were finally included in the meta-analysis. The factors that were found to predispose to IFIS significantly were male sex (odds ratio [OR], 4.25; CI, 2.58-7.01), hypertension (OR, 1.55; CI, 1.01-2.37), tamsulosin (OR, 31.06; CI, 13.74-70.22), finasteride (OR, 4.60; CI, 1.97-10.73), benzodiazepines (OR, 2.88; CI, 1.17-7.12), and antipsychotics intake (OR, 6.91; CI, 2.22-21.50). A decreased dilated pupil preoperatively was found predisposing to IFIS (weighted mean difference −0.93; CI, −1.19 to −0.67). Intracameral epinephrine, which was investigated as a potential prophylactic measure for preventing IFIS, did not reach statistical significance (OR, 0.29; CI, 0.08-1.06). A comprehensive preoperative assessment of all risk factors is vital to stratify the surgical risk, which is crucial in addressing IFIS because unanticipated IFIS could turn a routine surgery into one of significant visual morbidity.